Phosphate fertilization and critical leaf phosphorus content for okra - Souza, Arilson de J. F.; Wamser, Anderson F.; da Silva, Vitor B. [UNESP]; Nascimento, Sandra M. C.; Grangeiro, Leilson C.; Cecílio Filho, Arthur B. [UNESP] (My University, 2023)
The objective of this study was to evaluate the growth and yield of okra as a function of phosphorus (P) doses and to obtain the critical leaf P content, under the edaphoclimatic conditions of Maranhão (MA), Brazil. The field experiment was carried out from February 15, 2017, to May 9, 2017, in São Luís, MA. The experimental design was randomized blocks, with four replications. The treatments were doses of 0, 80, 160, 240 and 320 kg ha-1 of P2 O5, in the form of triple superphosphate, at planting, plus 10 t ha-1 of solid cattle manure. The increase of the P dose increased plant height, leaf dry mass and stem dry mass. With phosphorus supply, flowering occurred earlier than in plants without fertilization. Considering soils with low P content (P(resin) = 11 to 25 mg dm-3) and the minimum recommended organic fertilization for the okra crop of 10 t ha-1 of solid cattle manure, the maximum number of fruits, length of fruit and yield (9960.36 kg ha-1) were obtained with the fertilization of 80 kg ha-1 of P2 O5, for the edaphoclimatic conditions of MA, Brazil. The critical leaf P content in okra is 3.4 g kg-1.
Adubação fosfatada e teor crítico foliar de fósforo para o quiabeiro
Keywords: Abelmoschus esculentus; Foliar diagnosis; Mineral